APPROACES TO THE IMPORTANCE DENSITY CHOICE IN PARTICLE FILTERS - A. V. Parakhnevich; A. S. Solonar; S. A. Gorshkov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
There are spent three methods of importance density choice (Gaussian, kvasi-Gaussian and modified kvasi-Gaussian) for posterior density approximation using Monte Carlo numerical integration method and considered comparing Kalman filter and Particle Filter implementation in the report.